If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -15 = -45 + 60 Reorder the terms: -15 + 3x = -45 + 60 Combine like terms: -45 + 60 = 15 -15 + 3x = 15 Solving -15 + 3x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 3x = 15 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = 15 + 15 3x = 15 + 15 Combine like terms: 15 + 15 = 30 3x = 30 Divide each side by '3'. x = 10 Simplifying x = 10
| 3(x+2)=2[x-(4-x)] | | 4(x-6)-6(x-4)=x+4-(x-2) | | 2(w-5)-6w= | | 8y-7=19y+48 | | 13=41+x | | 5/8÷11/12 | | ((x)/(6))-3x-7=2 | | (x)/(6)-3x-7=2 | | 86+x=-48 | | sin^2x-6sinx=0 | | 11(x-4)=9(x+6) | | 100-3p=2p | | -6+7x=5x+10 | | 2x-25=-50 | | V-4.6=7.57 | | 3s^2+16+21=0 | | 6v=300 | | -14=6+4y | | 6=300 | | 6r^3+42r^2-18r=0 | | 3x+1.7+1.5=4.5x-16.3 | | -14.7=w/5-2.2 | | -x-4+3x=-5x-18 | | R^2+11r=-18 | | -2(8u-1)+3u=2(u+7) | | (3x+2)(4x-1)-(6x+2)(2x-1)=0 | | 4+3x=2+5(1-x) | | -4/3u=-28 | | ln(x)+ln(6x)=ln(7x) | | (y-5)*(y-8)=y^2+1 | | z^2-(i+3)z-2-2i=0 | | 3/-1= |